Indonesia : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Indonesia. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation discusses that the Indonesian economy performed well in 2018, despite external headwinds, including capital flow reversals. Growth stabilized above 5 percent and inflation eased to around 3 percent. A surge in imports and weak export growth contributed to a higher current account deficit. Growth is projected to remain stable over the medium term. Inflation is expected to remain within the target band and the current account deficit is expected to narrow gradually on lower imports. Risks are tilted to the downside and are mainly external. Reliance on portfolio inflows to finance the twin deficits leaves Indonesia vulnerable to capital flow reversals. Creating quality jobs for the young and growing population to harness Indonesia's demographic dividend requires a stronger impetus to growth, which has been constrained by structural weaknesses, including low tax revenues, shallow financial markets, and labor and product market rigidities.